1998
DOI: 10.1074/jbc.273.4.1917
|View full text |Cite
|
Sign up to set email alerts
|

The Stress Inducer Arsenite Activates Mitogen-activated Protein Kinases Extracellular Signal-regulated Kinases 1 and 2 via a MAPK Kinase 6/p38-dependent Pathway

Abstract: Cell response to a wide variety of extracellular signals is mediated by either mitogenic activation of the Raf/ MEK/ERK kinase cascade or stress-induced activation of the mitogen-activated protein kinase (MAPK) family members c-Jun N-terminal kinase/stress-activated protein kinase (JNK/SAPK) or p38. We have examined communications between these stress-and mitogen-induced signaling pathways.We show here that the stress cascade activator arsenite activates extracellular signal-regulated kinase (ERK) in addition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
154
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(162 citation statements)
references
References 26 publications
8
154
0
Order By: Relevance
“…The results shown are representative of three independent experiments p38 MAPK and AP-1 expression, binding and transactivation SF Rosenberger et al of p38 MAP kinase upregulates JNK activity. A similar interconnection between the di erent MAP kinase cascades has been demonstrated by Ludwig et al (1998) who found that arsenite induced activation of ERK-1/2 is mediated by p38 MAP kinase. The ability of MAP kinases to regulate the activity of their family members may be explained by their e ects on activating kinases and/or deactivating phosphatases as documented by the ®nding that p38 MAP kinase is involved in inhibition of the ERK-1/2 activating kinase MEK-1 in response to high concentrations of pervanadate (Daum et al, 1998).…”
Section: Discussionsupporting
confidence: 73%
“…The results shown are representative of three independent experiments p38 MAPK and AP-1 expression, binding and transactivation SF Rosenberger et al of p38 MAP kinase upregulates JNK activity. A similar interconnection between the di erent MAP kinase cascades has been demonstrated by Ludwig et al (1998) who found that arsenite induced activation of ERK-1/2 is mediated by p38 MAP kinase. The ability of MAP kinases to regulate the activity of their family members may be explained by their e ects on activating kinases and/or deactivating phosphatases as documented by the ®nding that p38 MAP kinase is involved in inhibition of the ERK-1/2 activating kinase MEK-1 in response to high concentrations of pervanadate (Daum et al, 1998).…”
Section: Discussionsupporting
confidence: 73%
“…43 A higher concentration, 500 M, of sodium arsenite also activated ERK1 and ERK2 in a p38-dependent manner during transformation of human HEK293 embryonic kidney cells. 44 This is, to our knowledge, the first report of the rapid inactivation of ERK1 and ERK2 by As 2 O 3 . Furthermore, MEK1 and MEK2, which act upstream of ERK, were also inactivated when U937 cells were treated with As 2 O 3 .…”
Section: Discussionmentioning
confidence: 61%
“…There appears to be a reasonably linear relationship between the degree of oxidative stress, the formation of disul®de species and the induction of stress responsive proteins. Thioredoxin has been the best characterized cysteine-rich redoxresponsive protein implicated in the regulation of several stress responsive proteins via direct or intermediate interactions (reviewed in Schulze-Ostho et al, 1995; Sen and Packer, 1996; Flohe et al, 1997; Kuo et al, 1995Cavigelli et al, 1996Ludwig et al, 1998Kilk et al, 1996Lim et al, 1997Duhe et al, 1998Krejsa et al, 1997Kang et al, 1998Lui et al, 1998 Piette et al, 1997). The recent identi®cation of thioredoxin as an inhibitor of stress kinase ASK1 (Saitoh et al, 1998), has shed new light on the modes of redox regulatable stress response.…”
Section: Ros-induced Modi®cation Of Redox Sensitive Proteins Which Rementioning
confidence: 99%